Improving patient and carer access to information and support through head and neck cancer treatment and survivorship using experience‐based co‐design. Issue 2 (31st October 2022) - Hiatt, Joanne; Young, Adrienne; Brown, Teresa; Banks, Merrilyn; Bauer, Judith
Abstract: Background: Previous studies have highlighted the unmet nutritional and supportive care needs of patients with head and neck cancer (HNC) and their carers from diagnosis and throughout the treatment and survivorship period. The aim of this study was to bring patients, carers and healthcare professionals together to co‐design a framework to improve access to nutrition information and support for patients and carers with HNC from diagnosis and throughout the treatment and survivorship period. Methods: Using experience‐based co‐design (EBCD), semistructured individual interviews were conducted with patients, carers and healthcare professionals to understand their experiences in accessing information and support outside of the hospital environment. Feedback events and co‐design workshops were held to prioritise areas for service improvement. Results: Participants (10 patients, 7 carers and 15 healthcare professionals) highlighted the importance of having consistent information and support recommendations from the multidisciplinary team. The two key areas for improvement identified through group and workshop events were linking reputable HNC resources to a HNC portal on the hospital website and the development of a series of short podcasts and video blogs with fact sheets attached presented by members of the multidisciplinary team, patients and carers at four time points spanning pretreatment and throughout the survivorship period. Conclusions: Using EBCD has enabled the co‐design of a framework for resource development with patients, carers and healthcare professionals to improve access to information and resources to support nutrition intake and supportive care needs for patients with HNC with their carers. Development and implementation of resources and evaluation of outcomes is ongoing. Abstract : Key point: Using experience‐based co‐design has enabled the co‐design of a framework for resource development to improve access to nutrition care information and support for patients with head and neck cancer and their carers.